2021
DOI: 10.1111/bjh.17612
|View full text |Cite
|
Sign up to set email alerts
|

British Society for Haematology guidelines for the management of adult myelodysplastic syndromes

Abstract: This document represents an update of the British Society of Haematology Guideline published in 2014 due to advances in understanding the biology and therapy of the myelodysplastic syndromes (MDS). 1 The objective of these guidelines is to provide healthcare professionals with clear guidance on the management of adult patients with MDS. Individual circumstances may dictate an alternative approach. A separate British Society for Haematology (BSH) guideline covers the Diagnosis and Evaluation of Prognosis of Adu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(33 citation statements)
references
References 135 publications
0
27
0
Order By: Relevance
“…If patients do not improve on appropriate antibiotics and the infectious work-up is noncontributory, it is important to consider other etiologies for respiratory failure. For example, pulmonary leukemic infiltration has been found to occur almost as frequently as pneumonia in this population on post-mortem examination [5]. Additionally, exacerbations of chronic lung disease, pulmonary edema, and drug toxicity can present in a similar fashion and are important differential diagnoses.…”
Section: Discussionmentioning
confidence: 93%
“…If patients do not improve on appropriate antibiotics and the infectious work-up is noncontributory, it is important to consider other etiologies for respiratory failure. For example, pulmonary leukemic infiltration has been found to occur almost as frequently as pneumonia in this population on post-mortem examination [5]. Additionally, exacerbations of chronic lung disease, pulmonary edema, and drug toxicity can present in a similar fashion and are important differential diagnoses.…”
Section: Discussionmentioning
confidence: 93%
“…Notably, the analysis by Lindsley et al suggested that more intensive conditioning may result in worse outcomes due to a higher risk of TRM without a reduction in relapse, presumably due to TP53 MDS being refractory to chemotherapy. Because of the low potential for cure, when available, transplant for TP53 mutated MDS should ideally be pursued in the context of a clinical trial focused on relapse reduction (17,29,53).…”
Section: Disease Related Prognostic Factorsmentioning
confidence: 99%
“…In patients with LR-MDS, life expectancy without transplant is on the order of years and, thus, the risks of alloBMT generally outweigh the potential benefits. However, some patients with LR-MDS based on IPSS or IPSS-R scoring should be considered for transplant in the setting of other high risk features including high risk clonal mutations such as TP53 , in the presence of significant bone marrow fibrosis, intolerance or contraindication to available therapies, and transfusion dependent patients who fail to achieve a hematologic response even after best available therapy ( 29 ). Additionally, because treatment options are limited after HMA and subsequent outcome are poor, our practice is to offer alloBMT to any patient with HMA failure regardless of disease risk stratification ( 30 ).…”
Section: Role and Considerations For Allogeneic Transplantmentioning
confidence: 99%
“…Clinically, this is an aggressive disease, behaving similarly to acute myeloid leukemia (AML). Treatment with hypomethylating agents is aimed towards slow progression to AML and should be started as soon as possible [ 3 ]. On the other hand, 90% of low-risk MDS experience anemia, which can lead to symptoms of fatigue, cardiac morbidity, and cognitive impairment [ 3 ].…”
Section: Introductionmentioning
confidence: 99%